2014
DOI: 10.1128/mmbr.00009-14
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Bacterial Microcompartment Organelles

Abstract: SUMMARY Bacterial microcompartments (MCPs) are sophisticated protein-based organelles used to optimize metabolic pathways. They consist of metabolic enzymes encapsulated within a protein shell, which creates an ideal environment for catalysis and facilitates the channeling of toxic/volatile intermediates to downstream enzymes. The metabolic processes that require MCPs are diverse and widely distributed and play important roles in global carbon fixation and bacterial pathogenesis. The protein shells o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
280
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 214 publications
(283 citation statements)
references
References 190 publications
(562 reference statements)
2
280
0
1
Order By: Relevance
“…Recent genomic analyses showed that nearly 40% of MCP-encoding species have genes for multiple MCP systems (1). Furthermore, the BMC domain proteins that form the shells of MCPs are homologous across the known types of MCP systems, including the Pdu, Eut, Grp, and carboxysome systems (5,6), and are understood to assemble via conserved edge complementarity. Given the widespread homology of MCP shell proteins and the BMC domain present in these proteins, it is likely that a myriad of other bacterial species which have the capacity to express multiple MCP systems (1) also have some mechanism to regulate proper assembly and function of these MCPs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent genomic analyses showed that nearly 40% of MCP-encoding species have genes for multiple MCP systems (1). Furthermore, the BMC domain proteins that form the shells of MCPs are homologous across the known types of MCP systems, including the Pdu, Eut, Grp, and carboxysome systems (5,6), and are understood to assemble via conserved edge complementarity. Given the widespread homology of MCP shell proteins and the BMC domain present in these proteins, it is likely that a myriad of other bacterial species which have the capacity to express multiple MCP systems (1) also have some mechanism to regulate proper assembly and function of these MCPs.…”
Section: Discussionmentioning
confidence: 99%
“…(19,20). The metabolic pathways, structure, and regulation of these MCPs have been the subject of a number of studies (5).The Pdu MCP consists of a protein shell that encapsulates 1,2-PD-degradative enzymes, and its function is to sequester a pathway intermediate (propionaldehyde) that is toxic and poorly retained by the cell envelope (19,(21)(22)(23). Production of Pdu MCPs is under the control of the regulatory protein PocR, and they are induced in the presence of 1,2-PD (24,25).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to this set of core enzymes, some bacteria possess several other auxiliary proteins that aid in the catabolism of ethanolamine (11). For example, members of the Enterobacteriaceae often utilize an alcohol dehydrogenase (EutG) that reduces acetaldehyde to ethanol and shell proteins (EutSMNLK), which form a microcompartment to encapsulate the ethanolamine-degrading enzymes (10,(12)(13)(14).…”
Section: Importancementioning
confidence: 99%